Conservation benefits of an interdisciplinary approach to marine mammal science - Lent, Rebecca J. (Frontiers in Marine Science, 2015)
Protected resource economists can greatly enhance the science and conservation of marine mammals, however such contributions are often hampered by a lack of understanding of the role of natural resource economics on behalf of more traditional marine mammal scientists. The three major threats to marine mammals - fishery bycatch, increasing underwater sound, and climate change could be more effectively addressed with an interdisciplinary approach that includes the full valuation of costs and benefits to society. Better management of these threats can be beneficial to humans as well as marine mammals.